A Multi-Center, Real-World Study of Chidamide for Patients With Relapsed or Refractory Peripheral T-Cell Lymphomas in China - Liu, Weiping; Zhao, Donglu; Liu, Ting; Niu, Ting; Song, Yongping; Xu, Wei; Jin, Jie; Cai, Qingqing; Huang, Huiqiang; Li, Zhiming; Hou, Ming; Zhang, Huilai; et al. (Frontiers in Oncology, 2021)
Chidamide has demonstrated significant clinical benefits for patients with relapsed/refractory (R/R) PTCL in previous studies. This multi-center observational study was aimed to evaluate the objective response rate (ORR), disease control rate (DCR), overall survival (OS), and safety of chidamide. From February 2015 to December 2017, 548 patients with R/R PTCL from 186 research centers in China were included in the study. Among the 261 patients treated with chidamide monotherapy, DCR was 89.3%, ORR was 58.6%, and 55 patients (21.1%) achieved complete response (CR). Among the 287 patients receiving chidamide-containing combination therapies, DCR was 90.2%, ORR was 73.2%, and 73 patients (25.4%) achieved CR. The median OS of all patients was 15.1 months. The median OS of patients receiving chidamide monotherapy and combination therapies was 433 and 463 days, respectively. These results demonstrate a significant survival advantage of chidamide treatments as compared with international historical records. Common adverse effects (AEs) were hematological toxicities. Most AEs in both monotherapy and combined treatments were grade 1–2. No unanticipated AEs occurred. In conclusion, chidamide-based therapy led to a favorable efficacy and survival benefit for R/R PTCL. Future studies should explore the potential advantage of chidamide treatment combined with chemotherapy.